Intervensi Pendidikan Melalui Penyuluhan Pencegahan Pernikahan Dini di Desa Paremas, Kecamatan Jerowaru, Lombok Timur - Wahidah, Ananda; Malik, Imam; Aryati, Risma Ade; Sumitro, Sumitro; Firmansyah, Agung; Noviana, Mila (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Early childhood marriage is a serious problem in West Nusa Tenggara, especially in East Lombok, with the incidence rate continuing to increase despite local regulations prohibiting it. The main factors that cause early marriage include low motivation to go to school, psychological conditions, and the economic conditions of parents who force children to marry young. Local cultures such as merariq kodek also reinforce this practice, where early childhood is seen as ready for marriage. The service activity was carried out through 2 stages, namely the preparation stage and the implementation stage of the activity on July 8, 2024, attended by 50 teenagers in Keranji Hamlet, Paremas Village, Jerowaru District. The counseling carried out by the service team from the Sociology Education Study Program, University of Mataram succeeded in increasing the awareness of the younger generation about the dangers of early marriage and the importance of education as the key to a better future. The results of the discussion also showed a change in positive attitudes, with participants unequivocally rejecting early marriage and agreeing to prioritize education. Efforts to educate and increase access to education need to continue to be strengthened as the main foundation to reduce the rate of early childhood marriage and form a quality generation in the future.